Cinematic imaginaries of the African city. (2nd January 2021) - Mupotsa, Danai S.; Moji, Polo B.; Himmelman, Natasha
ABSTRACT: This special issue unpacks the broad affective, aesthetic and material dimensions of African visuality, spatiality and temporality in cinematic imaginaries of the African city. The submissions evoke issues of specificity and materiality, reading the African city as cinematic form. They are situated within an interdisciplinary matrix that contributes to intellectual engagement with African cinemas through, among others, affect theory and the city as a matrix of feeling; critical black geography and the racialized construction city spaces; the urban as a temporal consciousness; and representations of social inequalities and urban geographies of exclusion. Through a range of genres the submissions unpack the histories, citizenships and sexualities that shape the cinematic imaginaries of Nairobi, Luanda, Johannesburg and Cape Town, concurrently reflecting on the erasure of the African city in Hollywoodian cinematic form.